Bioaugmentation and Propane Biosparging for In Situ Biodegradation of 1, 4‐Dioxane. Issue 2 (28th January 2015) - Lippincott, David; Streger, Sheryl H.; Schaefer, Charles E.; Hinkle, Jesse; Stormo, Jason; Steffan, Robert J.
Abstract Propane biosparging and bioaugmentation were applied to promote in situ biodegradation of 1, 4‐dioxane at Site 24, Vandenberg Air Force Base (VAFB), CA. Laboratory microcosm and enrichment culture testing demonstrated that although native propanotrophs appeared abundant in the shallow water‐bearing unit of the aquifer (8 to 23 ft below ground surface [bgs]), they were difficult to be enriched from a deeper water‐bearing unit (82 to 90 feet bgs). Bioaugmentation with the propanotroph Rhodococcus ruber ENV425, however, supported 1, 4‐dioxane biodegradation in microcosms constructed with samples from the deep aquifer. For field testing, a propane‐biosparging system consisting of a single sparging well and four performance monitoring wells was constructed in the deep aquifer. 1, 4‐dioxane biodegradation began immediately after bioaugmentation with R. ruber ENV425 (36 L; 4 × 109 cells/mL), and apparent first‐order decay rates for 1, 4‐dioxane ranged from 0.021 day−1 to 0.036 day−1. First‐order propane consumption rates increased from 0.01 to 0.05 min−1 during treatment. 1, 4‐dioxane concentrations in the sparging well and two of the performance monitoring wells were reduced from as high as 1090 µg/L to <2 µg/L, while 1, 4‐dioxane concentration was reduced from 135 µg/L to 7.3 µg/L in a more distal third monitoring well. No 1, 4‐dioxane degradation was observed in the intermediate aquifer control well even though propane and oxygen were present. The demonstration showed that propane biosparging and bioaugmentation can be used for in situ treatment of 1, 4‐dioxane to regulatory levels.